IMPLEMENTATION OF INMATE INTEGRATION SERVICES AS AN EFFORT TO REALIZE SOCIAL REINTEGRATION IN CLASS IIA PRISON KEDIRI - Salman Alfarizi Arya Putra; Naniek Pangestuti (Universitas Nusa Cendana, 2026)
The study employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving correctional officers and inmates. The analysis was conducted using the Miles and Huberman model and supported by thematic analysis. The findings reveal that integration service policies have generally been implemented in accordance with established standards. However, their effectiveness remains limited due to several constraints, including overcapacity conditions, a shortage of correctional officers, weak coordination with external stakeholders, and low levels of social support for inmates. These results highlight the importance of strengthening resource capacity, improving inter-agency collaboration, and enhancing social support systems to ensure the success of inmate reintegration into society. Keywords: Prisoner Integration; Social Reintegration; Corrections; Policy Implementation